Il matrimonio e la famiglia nel Codice civile italiano: un'analisi contrastiva dei termini e delle espressioni del C.C. del 1942 e del C.C. aggiornato nel 2022 - Kucharska, Anna (Neofilolog, 2023)
The purpose of this article is to analyse the image of the family in the Italian Civil Code. This study is carried out from a linguistic point of view. Passages on the family will be analysed in order to present the roles of the man and woman in marriage. The terminological evolution will be shown by comparing the 1942 Code and the 2022 Code. The aim of the study is to point out how the analysis of a legal text can contribute to a better understanding of a country's culture.